(untitled) (Bulletin of Pure and Applied Sciences-Chemistry, 2022)
Underground water characterizes a significant resource of drinking water along with its quality is presently threatened via a mixture of microbiological and chemical pollution. The current work is completed to assess underground water quality for the idea of drinking with domestic consumptions via correlation analysis on the bank of river Ramganga. The assessment was fined out in support of two continuous years (2020-2021) in rains along with winter seasons. The statistical facts expect as underground water quality is not appropriate for drinking usage in present region.